Antibiotics in pediatrics - parental knowledge and attitudes - Trkulja, Maja G; Vidović, Anica LJ; Božić, Bojana (Medicinski podmladak, 2017)
Introduction: Antibiotics represent the most prescribed class of medication in the pediatric circles. Almost 50% of the medication was prescribed without definite merit. Recently published studies have shown that the level of knowledge, awareness, as well as parents’ expectations play a significant role in the amount of prescribed antibiotics by pediatricians. Aim: To assess the level of parent’s education, attitude and behavior in regard to antibiotic use in pediatric population in Serbia. Material and methods: The cross-sectional study was performed between October 2015 and February 2016. An anonymous survey approach had been used. Demographic data of the participants gave an insight in the level of knowledge and common practice regarding the use of antibiotics in children. The data collected was analyzed by methods of descriptive and analytic statistics. Results: Of 850 recruited, 763 completed and returned the survey. A high level of knowledge was found in 79.5% of the participants. The highest percent of parents answered the questions correctly in regard to reporting drug-related adverse reactions, including allergic reactions (99% and 93% respectively). Almost one third (27%) of the parents thought that antibiotics can cure viral infections. More than 20% of participants thought that antibiotics can control pain, and that more expensive medication was more effective. The worrisome is the fact that 15% bought antibiotic at least once without a doctor’s prescriptions, while 18% stashed away leftovers for later use. Conclusion: Although study results showed good quality data, parents are still deciding by themselves to start antibiotic therapy. Reinforcing established educational programs and encouraging communication with their pediatrician would be highly justified. Key words: antibiotics, knowledge, attitudes, parents, children.